Disrupting deficit mindsets: mitigating cognition that derails equitable continuous improvement - Hinnant-Crawford, Brandi N.; Childs, Rebecca G.; Owusu Achiaw, Augustine (Frontiers in Education, 2025)
IntroductionContinuous improvement (CI) has transformative potential but far too often that potential is unrealized. Practitioners engaging in CI are frequently guided by mindsets that derail system transformation by shifting the focus from improving systems to fixing people.MethodsEmploying multiple data sources (document analysis of dissertations in practice and interviews) this multi-case study examines nine cases of scholar-practitioners engaging in CI work and how they mitigated the impact of deficit mindsets.ResultsCross-case analysis revealed four strategies for disrupting deficit ideology in CI work: composing intentional teams, building team capacity, employing critical theory, and involving those impacted.DiscussionImplications for engaging in CI and teaching CI are discussed.